HUBUNGAN SABAR DAN HARGA DIRI DENGAN AGRESIVITAS PADA SUPPORTER BOLA - Eka Sari Oktaviani; Rizka Dara Vonna; Yuanita Caroline Yuanita Caroline (Psikoislamedia : Jurnal Psikologi, 2017)
This research was conducted to find out the relationship between the patient and self-esteem with the aggressiveness of a football supporters because many phenomena that occur as a result of the aggressive behavior of soccer supporters that are often negative and harming others. The subjects in this research there were as many as 102 football supporters with snow ball sampling technique. This study used three scales, the scale of patience, self-esteem scale and scale of agressiveness. Form of the scale used is Likert scale. Hypothesis testing is done by using multiple regression of analysis. The results showed that the analysis results sig 0.000 < 0.05, or higher score of patience and higher score of self-esteem in a football supporter, can be a predictor of low score of aggressiveness.